Structure-Morphological and Electroconductive Properties of Carbon Materials Based on Saccharose and Citric Acid - Mandzyuk, V. I.; Mironyuk, I. F.; Kulyk, Yu. O. (Physics and Chemistry of Solid State, 2020)
The article explores the effect of citric acid as a pore-forming agent on the structure, morphology and electroconductive properties of porous carbon materials (PCMs) obtained from carbon precursor (saccharose) using the methods of small-angle X-ray scattering, low-temperature porometry and impedance spectroscopy. It was found that the volumetric fractal structure is formed in the samples, and the fractal dimension Dv decreases from 2.15 to 1.91 with the addition of citric acid due to surface loosening. It was set that the use of 20 wt.% of citric acid causes the most effective modification of the porous structure of the material, i.e. an increase in specific surface area of 1.35 times, total pore volume of 1.14 times and a significant development of micro- and mesoporosity. It is shown that the use of citric acid as a pore-forming agent leads to an increase in the specific electrical conductivity of PCMs almost 5 times.